Pattern of Cervical Lymph Node Metastasis in Squamous Cell Carcinoma of Buccal Mucosa and Its Correlation for Optimal Neck Management - Raza, Syeda Hala; Ahmed, Sufyan; Tahir, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To document cervical node metastasis in oral squamous cell carcinoma (OSCC) of buccal mucosa and analyze the oncological necessity of most suitable neck dissection, in population of a tertiary care hospital. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Maxillofacial department, Abbasi Shaheed Hospital, Karachi Pakistan, from Jul 2018 to Jul 2020. Methodology: It was a study of 110 histopathologically proven patients of Oral Squamous Cell Carcinoma of buccal mucosa. Non-probability sampling technique was used and sample size was calculated with help of WHO software using 8% prevalence of cervical metastasis in oral squamous cell carcinoma of buccal mucosa, 95% confidence interval, 7% margin of error. Patients aged 18-75 years, either gender, resectable tumor with or without lymph node involvement were included. Patients treated previously, with distant metastasis, unfit for general anesthesia and not willing to give consent were excluded. Tumor resection with selective neck dissection was done by one experienced surgeon and specimens were sent to same laboratory for histopathology. Data was collected on a proforma and analyzed using SPSS version 26. Result: Out of 110 patients 93 (84.5%) were male and 17 (15.5%) were female. Mean age was 43 years ± 12.75. Occurrence of occult metastasis was 41.8%. According to histopathologically positive metastatic node, highest incidence was in level I 21 (19.1%) followed by levels I, II, III 12 (10.9%) and levels I-II 7 (6.4%), while positive levels I, II, III, IV were seen in only 2 (1.8%) cases. Conclusion: Oral Squamous Cell Carcinoma.............